Решите уравнение пожалуйста:
а)(х-3)(х+2)-(х-1)(х+1)=3х+7
б) (х+4)2-(х+1)(х-2)=2х-3

2

Ответы и объяснения

2014-04-14T16:55:01+00:00
А) х2+2х-3х-6-х2-х+х+1=3х+7
 х2+2х-3х-6-х2-х+х+1-3х-7=0
-4х-12=0
-4х=12
х=12:(-4)
х=-3
б) 2х+8-х2+2х-х+2=2х-3
2х+8-х2+2х-х+2-2х+3=0
-х2+х+13=0
х1+х2=-1-по теореме Виетта
х1*х2=13-по теореме Виетта
х2-это х в квадрате. 
  • 2407Alexa
  • почетный грамотей
2014-04-14T17:03:41+00:00
X²+2x-3x-6-x²+1-3x=7 -4x=7+6-1 -4x=12|:(-4) x=-3 x²+8x+16-(x²-2x+x-2)-2x=-3 x²+8x-x²+2x-x-2x=-3-16-2 7x=-21|:7 x=-3